A statistical quality control study on HLF Products - Lanquino, Melanie; Mercado, Karen; Ramos, Katrina Fe (Quezon City College of Engineering, University of the Philippines Diliman, 2006)
A quality control study is performed on HLF Products during the period from August to September 2006. After documenting the necessary facts about the company - its production line, ingredients or raw materials, equipment, manpower, production process, and other vital aspects that group sees to be related to the quality system of the company, the group observed problems in the production process. This includes the variable weights in the Siopao production. HLF Products' product lines also include dim sum food like siomai, fish balls, and squid balls, etc. but the group will focus on the Siopao production due to its production volume and the market potential. The results from the FMEC Analysis clearly point out two major aspects of production that the company should focus on; Product consistency because this is the, only way to ensure that their products are of good quality. Consequently, this would also assure that the customers are satisfied with their product and would continue to patronize it. The proponents employed X-R charts using MINITAB for the problem on individual weights to determine the extent of variability in the process. It is found out that the process is under statistical control for Siopao Bola Bola and Sweet Pork. However, in the Siopao X-R chart, a point is beyond the upper control limit and a trend signifies a cause. Additional in-depth analysis is done on this trend to find the assignable causes that can account for the pattern. Also, Cp is equal to 0.97 which is below the recommended minimum of 1.33 for existing processes. The main causes identified are the lack of supervision and the production method itself. The study proponents then consider the financial viability of providing additional operation supervision and revising the production processes. The group also employs the Quality Functional Deployment to translate the customer quality requirements into designs characteristics.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial quality control.
Keywords: Dim sum; Quality control